The relationship between PM2.5 and the onset and exacerbation of childhood asthma: a short communication - Zhang, Yue; Yin, Xixi; Zheng, Xiangrong (Frontiers in Pediatrics, 2023)
Much is known about the link between air pollution and asthma in adults, particularly PM2.5. Studies have found that certain levels of fine particulate matter (PM2.5) can increase airway responsiveness and worsen asthma. PM2.5 may play a role in the onset and exacerbation of childhood asthma. However, there is little in the literature on how PM2.5 affects asthma attacks and exacerbations in children. Asthma is a common chronic disease in children, and air pollution can aggravate it. The effect of PM2.5 on childhood asthma needs further research. By evaluating, reviewing and collating existing results in this area, this paper aims to explore the relationship between PM2.5 and asthma onset and exacerbation in children.For requirements for a specific article type please refer to the Article Types on any Frontiers journal page. Please also refer to Author Guidelines for further information on how to organize your manuscript in the required sections or their equivalents for your field 1 .Asthma is an chronic inflammatory disease of the airways, and is associated with bronchial hyperresponsiveness, reversible airflow limitation, recurrent wheezing, chest tightness, and coughing [1].Asthma is thought to be caused by a combination of genetic and external factors [2].In addition to individual genetic profiles, abnormal environmental stimuli, such as exposure to air